2021
DOI: 10.1051/0004-6361/202141417
|View full text |Cite
|
Sign up to set email alerts
|

The effect of active galactic nuclei on the cold interstellar medium in distant star-forming galaxies

Abstract: In the framework of a systematic study with the ALMA interferometer of IR-selected main-sequence and starburst galaxies at z ∼ 1 − 1.7 at typical ∼1″ resolution, we report on the effects of mid-IR- and X-ray-detected active galactic nuclei (AGN) on the reservoirs and excitation of molecular gas in a sample of 55 objects. We find widespread detectable nuclear activity in ∼30% of the sample. The presence of dusty tori influences the IR spectral energy distribution of galaxies, as highlighted by the strong correl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 135 publications
(192 reference statements)
1
16
0
Order By: Relevance
“…Finally, by contrast with early PDR models suggesting that [C I] is emitted from a thin layer around molecular clouds, both observational studies (Plume et al 1994, Ikeda et al 1999 and more recently Popping et al 2017, Nesvadba et al 2019, Valentino et al 2020 as well as theory and simulations (Papadopoulos et al 2004, Offner et al 2014, Gaches et al 2019, Heintz & Watson 2020 have shown a strong correlation between [C I] emission and that from CO isotopologues, likely resulting from turbulence within clouds. The turbulence produces a complex geometry with many internal surfaces and FUV pathways to dissociate the CO and excite [C I].…”
Section: Observations On Galaxy Scalesmentioning
confidence: 58%
See 2 more Smart Citations
“…Finally, by contrast with early PDR models suggesting that [C I] is emitted from a thin layer around molecular clouds, both observational studies (Plume et al 1994, Ikeda et al 1999 and more recently Popping et al 2017, Nesvadba et al 2019, Valentino et al 2020 as well as theory and simulations (Papadopoulos et al 2004, Offner et al 2014, Gaches et al 2019, Heintz & Watson 2020 have shown a strong correlation between [C I] emission and that from CO isotopologues, likely resulting from turbulence within clouds. The turbulence produces a complex geometry with many internal surfaces and FUV pathways to dissociate the CO and excite [C I].…”
Section: Observations On Galaxy Scalesmentioning
confidence: 58%
“…The whole CO ladder of AGN host sources can be another valuable tool to infer the presence of an XDR component contributing to the gas heating (Bradford et al 2009, Hailey-Dunsheath et al 2012, Pozzi et al 2017, Mingozzi et al 2018, Valentino et al 2021 as XDRs are characterized by large column densities of warm molecular gas, where high-J CO lines (J 8) can be efficiently excited. For this reason the CO Spectral Line Energy Distribution (SLED) resulting from XDR models peaks at increasingly higher J for increasing X-ray flux (Vallini et al 2019, and see Figure 8), even though CO emission can be suppressed by X-ray induced CO dissociation (Section 4.4) at intermediate column densities (Kawamuro et al 2020).…”
Section: Diagnostic Plotsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent literature is still somewhat divided on the topic of the impact of AGN on the molecular gas reservoir of their hosts. For example, Valentino et al [158] examine the ALMA CO properties of both mid-IR and X-ray AGN and find no significant effect in either amount of molecular gas or its excitation. On the other hand, Circosta et al [159] find that, controlling for other parameters such as stellar mass and star-formation rate, AGN hosts have lower CO 3-2 luminosities suggestive of either gas removal or excitation to higher rotation states.…”
Section: Gas Properties Around Agnmentioning
confidence: 99%
“…Kereš et al 2005;Dekel et al 2009), (2) AGN or stellar feedback, especially in massive galaxies (e.g. Weiner et al 2009;Steidel et al 2010;Kakkad et al 2020;Valentino et al 2021), and (3) heating of the gas reservoir in the CGM (e.g. Schawinski et al 2014).…”
Section: The Hi Depletion Timescalementioning
confidence: 99%